1996
DOI: 10.1152/jappl.1996.80.2.452
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine counteracts the ergogenic action of muscle creatine loading

Abstract: This study aimed to compare the effects of oral creatine (Cr) supplementation with creatine supplementation in combination with caffeine (Cr+C) on muscle phosphocreatine (PCr) level and performance in healthy male volunteers (n = 9). Before and after 6 days of placebo, Cr (0.5 g x kg-1 x day-1), or Cr (0.5 g x kg-1 x day-1) + C (5 mg x kg-1 x day-1) supplementation, 31P-nuclear magnetic resonance spectroscopy of the gastrocnemius muscle and a maximal intermittent exercise fatigue test of the knee extensors on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0
12

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(124 citation statements)
references
References 17 publications
4
108
0
12
Order By: Relevance
“…Changes in daily physical activity (Robinson et al 1999) as well as caffeine consumption were controlled during the course of the study by urging participants to maintain their normal daily activities, dissolve the powdered substance in non-caffeinated beverages, and abstain from caffeine for 1 h prior to neuromuscular testing. It has been reported that caffeine alters contractile properties (Fryer & Neering, 1989;Nehlig & Debry, 1994) and may decrease Cr uptake (Vandenberghe et al 1996). Exclusion criteria involved creatine supplementation within the previous 12 months, myopathies or neuromyopathies, diabetes, alcoholism and physical activity patterns which were deemed to represent highly trained men.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in daily physical activity (Robinson et al 1999) as well as caffeine consumption were controlled during the course of the study by urging participants to maintain their normal daily activities, dissolve the powdered substance in non-caffeinated beverages, and abstain from caffeine for 1 h prior to neuromuscular testing. It has been reported that caffeine alters contractile properties (Fryer & Neering, 1989;Nehlig & Debry, 1994) and may decrease Cr uptake (Vandenberghe et al 1996). Exclusion criteria involved creatine supplementation within the previous 12 months, myopathies or neuromyopathies, diabetes, alcoholism and physical activity patterns which were deemed to represent highly trained men.…”
Section: Subjectsmentioning
confidence: 99%
“…Most studies report an increase in isotonic dynamic strength following Cr supplementation (Earnest et al 1995;Gordon et al 1995;Vandenberghe et al 1996), but the few studies of isometric strength are controversial. Our results of isometric elbow flexion strength are similar to those of van Leemputte et al (1999).…”
Section: Maximal Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Todos os atletas foram orientados a manter seus hábitos alimentares e rotina de treinos durante o período de suplementação, evitando qualquer outra e bebidas cafeinadas (café, chocolate, mate, pó de guaraná, bebidas energéticas, coca-cola e guaraná), uma vez que a cafeína parece anular o efeito da creatina (9) . A ingestão de água foi ad libitum.…”
Section: Métodosunclassified
“…Vandenberghe et al 28 , em um estudo comparativo entre os efeitos da suplementação oral de creatina e de creatina em combinação com cafeína, de-monstrou que os efeitos ergogênicos da creatina no aumento da força, durante a execução de exercícios intensos realizados de modo intermitente, foram eliminados no grupo que ingeriu também a cafeína.…”
Section: Cafeína E Esporteunclassified